2003
DOI: 10.4049/jimmunol.170.11.5391
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Cytotoxic Responses in Mice and Human Individuals Against Hematological Malignancies Using Survivin-RNA-Transfected Dendritic Cells

Abstract: Survivin is a member of the inhibitors of apoptosis family and is overexpressed in many types of human cancers, making it an attractive target for T cell-based immunotherapeutic strategies. Recently, HLA-A2-binding peptides derived from the survivin protein were identified as capable of inducing specific T cell responses in cancer patients. Here we demonstrate that human survivin-specific CTLs generated from PBMC by stimulation with autologous dendritic cells transfected with survivin-RNA were cytotoxic for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 12 publications
1
56
1
1
Order By: Relevance
“…More specifically, Zeis et al [24] have shown that transfection of dendritic cells (DC) with survivin mRNA leads to resistance to tumor challenge. Xiang et al [25] showed that a DNAbased survivin vaccine could produce a CTL response against Lewis lung carcinoma with regression of both primary tumor and pulmonary metastases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, Zeis et al [24] have shown that transfection of dendritic cells (DC) with survivin mRNA leads to resistance to tumor challenge. Xiang et al [25] showed that a DNAbased survivin vaccine could produce a CTL response against Lewis lung carcinoma with regression of both primary tumor and pulmonary metastases.…”
Section: Discussionmentioning
confidence: 99%
“…This is a further indicator of the natural processing of survivin into potentially immunogenic epitopes, not previously described. The fact that immune response to SVN [18][19][20][21][22][23][24][25] , SVN 39-46 , SVN [9][10][11][12][13][14][15][16] , SVN 97-104 peptides were not detected in these animals could be attributed to one or more of the following: i) suboptimal class I binding by these peptides, ii) lack of adequate T cell receptor interaction with the peptides in the context of class I, and iii) lack of appropriate processing of the survivin protein. Immunotherapy has emerged as a potential treatment modality for cerebral gliomas because it is: (i) specific to tumor cells, (ii) has the potential to eradicate infiltrating tumor cells after surgical debulking, and (iii) may be capable of eliciting a long-lasting memory response to prevent tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…There is accumulating evidence that APC transduced with in vitro transcribed mRNA encoding certain Ag are potent inducers of CTL specific to tumor-associated Ag [21][22][23][24], even overcoming immunological tolerance to self Ag [25]. The advantages seem to derive from (1) complete deletion of antigenicity of vector backbone sequences; (2) highly reproducible yields with in vitro transcription; (3) high efficiency of transduction using electroporation.…”
Section: Introductionmentioning
confidence: 99%
“…[140][141][142] Survivinspecific cytotoxic T-cell responses could be generated against human acute myeloid leukemia blasts and against murine lymphoma in an engraftment model. 143,144 The potential of Livin for immunotherapy is investigated in melanoma. 145 Of the IAP-regulating proteins, SMAC is investigated for its therapeutic potential in cancer.…”
Section: Iaps As Targets For Cancer Therapymentioning
confidence: 99%